Methyleugenol, a major metabolite on culture of endophytic fungi isolated from pandan wangi plant - Yuliasri Jamal (Indonesian Journal of Pharmacy, 2009)
Two kinds of endophytic fungi i.e. Colletotricum sp. PWD2 and Coelomycetes PWA1 isolated from pandan wangi (Pandanus amarylifolius) have been cultivated in a liquid medium, GYP for 3 weeks at room temperature without agitation. The ethyl acetate extracts derived from liquid cultures showed antifungal activity against Saccharomyces cerevisiae. The GC-MS analysis results showed methyleugenol as main metabolite in the ethyl acetate extract of both fungi cultures.Key words: pandan wangi, Pandanus amarylifolius, endophytic fungi, antifungal, methyleugenol